Pengaruh Disiplin Kerja, Motivasi Kerja dan Kompensasi Terhadap Kinerja Pegawai Dinas Pariwisata Bantul DIY - Nadia, Silvi; Yuliantoharinugroho, Yuliantoharinugroho (LPPM AKADEMI MANAJEMEN ADMINISTRASI YOGYAKARTA, 2024)
This research aims to analyze the influence of work discipline, work motivation and compensation on the performance of employees of the Bantul DIY Tourism Office. This research uses quantitative research methods. The population of this study was all employees of the Bantul DIY Tourism Office, namely 50 people. To determine the sample for this study, a saturated sampling technique was used in which the entire population was sampled in this study. This research data was obtained through a questionnaire which was analyzed using multiple linear analysis, the research results showed that: Work discipline does not have a positive effect on employee performance which has a t-count value (0.565) < t-table (2.012) and a significant level (0.575) > (0.05). Work motivation does not have a positive influence on employee performance which has a calculated t-value (1.993) < t-table (2.012) and a significant level (0.052) > (0.05). Compensation has a positive effect on employee performance which has a t-count value (2.773) > t-table (2.012) and a significant level (0.008) < (0.05). And simultaneously the variables work discipline (X1), work motivation (X2), and compensation (X3) influence employee performance (Y) which has a calculated F value (5.491) > F table (2.81) and a significant level (0.003) < (0.05).